Evolution of Antimicrobial Resistance in Klebsiella pneumoniae over 3 Years (2019-2021) in a Tertiary Hospital in Bucharest, Romania - Alexandra Cireșă; Daniela Tălăpan; Carmen-Cristina Vasile; Cristina Popescu; Gabriel-Adrian Popescu (MDPI AG, 2024)
Background: The antimicrobial resistance (AMR) of Klebsiella pneumoniae recorded a steep upward trend over the last two decades, among which carbapenem-resistant Klebsiella pneumoniae (CRKP) is one of the most concerning strains considering the development and spread of AMR. The aim of this study was to analyze the evolution of AMR for Klebsiella pneumoniae and to describe the risk factors of AMR for Klebsiella pneumoniae, including the COVID-19 pandemic. Methods: We conducted a retrospective study on Klebsiella pneumoniae non-duplicative isolates collected from patients admitted to a tertiary hospital in Bucharest, Romania, from January 2019 to December 2021. We evaluated AMR changes by comparing resistance between 2019 and the mean of 2020-2021. Results: The rates of AMR increased for third-generation cephalosporins, carbapenems, aminoglycosides, fluoroquinolones, and colistin and decreased for trimethoprim/sulfamethoxazole (TMP/SMX), 45.7% in 2019 vs. 28.3% in 2021. A longer length of hospital stay (ꭓ2 = 49.68, p < 0.01); recent antibiotic consumption, RR = 1.38, 95% CI [1.21, 1.57]; and recent contact with hospital settings, RR = 1.54, 95% CI [1.32, 1.8] were risk factors for multidrug-resistant (MDR) Klebsiella pneumoniae. Conclusions: The AMR of Klebsiella pneumoniae increased during 2020-2021 for most of the potential active antibiotics; only TMP/SMX resistance decreased, and it may represent a treatment option for CRKP or MDR Klebsiella pneumoniae infections. Decreasing the excessive use of antibiotics and the implementation of prevention and control measures in healthcare settings are mandatory for avoiding further increases in the AMR rate of Klebsiella pneumoniae.